A novel mass assay to measure phosphatidylinositol-5-phosphate from cells and tissues. Issue 10 (21st October 2019) - Ghosh, Avishek; Sharma, Sanjeev; Shinde, Dhananjay; Ramya, Visvanathan; Raghu, Padinjat
Abstract: Phosphatidylinositol-5-phosphate (PI5P) is a low abundance lipid proposed to have functions in cell migration, DNA damage responses, receptor trafficking and insulin signalling in metazoans. However, studies of PI5P function are limited by the lack of scalable techniques to quantify its level from cells and tissues in multicellular organisms. Currently, PI5P measurement requires the use of radionuclide labelling approaches that are not easily applicable in tissues or in vivo samples. In the present study, we describe a simple and reliable, non-radioactive mass assay to measure total PI5P levels from cells and tissues of Drosophila, a genetically tractable multicellular model. We use heavy oxygen-labelled ATP ( 18 O-ATP) to label PI5P from tissue extracts while converting it into PI(4, 5)P2 using an in vitro kinase reaction. The product of this reaction can be selectively detected and quantified with high sensitivity using a liquid chromatography-tandem mass spectrometry (LC-MS/MS) platform. Further, using this method, we capture and quantify the unique acyl chain composition of PI5P from Drosophila cells and tissues. Finally, we demonstrate the use of this technique to quantify elevations in PI5P levels, from Drosophila larval tissues and cultured cells depleted of phosphatidylinositol 5 phosphate 4-kinase (PIP4K), that metabolizes PI5P into PI(4, 5)P2 thus regulating its levels. Thus, we demonstrate the potential of our method to quantify PI5P levels with high sensitivity from cells and tissues of multicellular organisms thus accelerating understanding of PI5P functions in vivo .